Using so-called mind-body practices to promote youths' well-being: Reflections on therapeutic outcomes, strategies, and processes. Issue 2 (2nd April 2016) - Renshaw, Tyler L.
Abstract : The present article provides commentary on this pioneering special issue covering the usefulness of so-called mind-body practices with youth and in schools. I begin by addressing the way we talk about this approach to practice, describing a few undesirable consequences that can follow from using the mind-body moniker adopted from the world of medicine, and then calling for new verbal framings that are grounded in scientific psychology and education. The remainder of the commentary discusses three critical issues that run throughout the articles in this special issue: specifically, the therapeutic outcomes, strategies, and processes associated with so-called mind-body practices. Ultimately, I conclude that mind-body practices are likely broadly useful for promoting youths' well-being outcomes in schools, that many of these practices appear to share the common therapeutic strategy of mindfulness training, and that increased attention is warranted toward identifying the therapeutic processes that drive these practices. Along the way, I also offer an optimistic response to skeptical critiques of mindfulness training raised in this special issue, encouraging readers to further consider the bulk of empirical evidence available via recent systematic reviews and meta-analyses.